Construction of a public policy for the training of educators - Sánchez Jaramillo, César Enrique
This work presents an overview that covers the legal and normative foundations and some proposals that, in terms of training of trainers, are part of the state of the art. It also includes the contributions resulting from a national forum on the theme developed by the National Ten-Year Education Plan and raises the reflection on the possible characteristics of a Teacher Training System. It also briefly includes some of the ideas presented by the authors of this edition of SENA Training Routes Review.